Di-n-butyl and di-iso-pentyl phthalates and their mixture increase oxidative stress and embryo-larval malformations in zebrafish (Danio rerio) - Juliana Roratto Lirola; Tathyana Benetis Piau; Daniela Moraes Leme; Anderson Joel Martino Andrade; Izonete Cristina Guiloski; Helena Cristina Silva de Assis; Cesar Koppe Grisolia; Marta Margarete Cestari (Genetics and Molecular Biology)
Abstract Different phthalate compounds, known as emerging contaminants, such as Di-n-butyl (DBP) and di-iso-pentyl (DiPeP) phthalates, have been found in aquatic environments and are widely used as additives to increase the flexibility of plastics. This study intended to evaluate the toxicity in zebrafish embryos and larvae of DBP and DiPeP, as well as the mixture of the two compounds. Fish embryo toxicity, neurotoxicity, oxidative stress, and genotoxicity studies were carried out in Danio rerio (zebrafish) embryos and larvae. Fish were exposed to DBP and DiPeP in concentrations ranging from 0.001 to 0.125 mg/L and also a combination of compounds DBP + DiPeP (1:1 MIX). DBP caused mortality and embryo malformations from 0.062 mg/L, DiPeP at 0.125 mg/L and the mixture at 0.031 mg/L, indicating the potential toxicity of these phthalates. Isolated phthalates and in mixture induced neurotoxicity and oxidative stress, at low concentrations in zebrafish larvae. No genotoxicity was found through comet assay in larvae. DBP was more toxic than DiPeP, and the mixture was more toxic than both phthalates when tested in isolation, showing some kind of interaction.